The Lean Course Canvas - Ely, Philip (Curtin University, 2017)
The 'Lean Course Canvas' and accompanying 'Course Canvas Scorecard' is a tool designed for academics and administrators in the development of new course offerings. Building on concepts emergent from the world of lean business modelling, the Lean Course Canvas was trialled in the Curtin University 'Courses of the Future Hackathon' in 2017.